(untitled) (Bangladesh Journal of Pharmacology, 2012)
This work evaluates the cardioprotective potential of dietary coconut sprout (Cocos nucifera Linn.) on isoproterenol induced myocardial infarction in rats. Male Sprague Dawley rats were pretreated with coconut sprout (50, 100 and 200 mg/100 g body weight) orally for 45 days and then cardiotoxicity was induced with isoproterenol (20 mg/100 g body weight) twice at an interval of 24 hours. Activity of cardiac marker enzymes were significantly increased in the serum and decreased in the heart of isoproterenol treated rats indicating cardiac damage. These effects were significantly reduced in coconut sprout pretreated rats. Moreover, pretreatment with coconut sprout increased anti-oxidant status and decreased oxidative stress in the heart. Histopathological examination revealed almost normal tissue morphology in the heart of these rats. These observed beneficial effects indicate that coconut sprout possesses significant cardioprotective and antioxidant properties.